AMMI analysis of genotype × environment interaction on seed yield of confectionary sunflower (Helianthus annuus L.) genotypes: AMMI ANALYSIS OF GENOTYPE × ENVIRONMENT ON SEED YIELD OF CONFECTIONARY SUNFLOWER - M S UMA; S D NEHRU; M S UMAR FAROOQ; DATTATRAYA BHAT; K M SRIVINAS REDDY; C P MANJULA; K S SOMASHEKAR (Journal of Oilseeds Research, 2021)
In this study, 60 confectionary sunflower genotypes were grown for three successive years during kharif 2018, 2019 and 2020 to determine the seed yield stability and adaptability over years. Yield stability and adaptability were analysed by combined analysis and AMMI model. The significant interaction indicated that the genotypes respond differently across the different environments. In AMMI analysis, the AMMI 1 biplot showed the genotype EC 734790 exhibited highest seed yield with 22.95g and high protein content of 31.23% and low oil content of 21.15% which is favoured for confectionary type of sunflower and is stable than all other varieties over all the three successive years, along with this the genotypes EC 734790, EC 734831, EC 734844 and EC 734814 had higher mean yields with high main (additive) effects. The results of the study further indicated that, the stable genotypes for seed yield over three successive years were G54- EC 734790 (22.95g) >G55- EC 734831(19.57g) >G56- EC 734844(18.15g) >G26- EC 734814(19.38g) with the help of AMMI model of stability analysis. Hence, these genotypes would be considered as more adapted to a wide range of environments over three different years than the rest of genotypes.